2021
DOI: 10.4081/jphr.2021.2279
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Psychological Distress among Myanmar Residents during Covid-19 Pandemic Crises

Abstract: Background: COVID-19 pandemic reached a public health emergency status of international concern. The impacts and events associated with this were associated with adverse psychological impacts among the general public globally. This study aimed to determine the prevalence of psychological distress and to identify predictors associated with psychological distress due to the COVID-19 pandemic among the population in Myanmar.Design and Methods: A cross-sectional survey was conducted from March to April 2020 among … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…Studies have unanimously agreed that COVID-19 has severe health repercussions, including quality of life ( 14 ), mental health ( 15 19 ), and psychological distress ( 20 25 ). Misinformation and vaccine efficacy also impacted the global COVID-19 vaccination program, driving vaccine hesitancy ( 26 28 ).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have unanimously agreed that COVID-19 has severe health repercussions, including quality of life ( 14 ), mental health ( 15 19 ), and psychological distress ( 20 25 ). Misinformation and vaccine efficacy also impacted the global COVID-19 vaccination program, driving vaccine hesitancy ( 26 28 ).…”
Section: Introductionmentioning
confidence: 99%
“…Also, a higher percentage of respondents (63.5%) in a study carried out by [34], respondents did not suffer any distress due to the pandemic. It was also reported by [35] al in their study among Myanmar residents that 62.6% of the respondents suffered psychological distress because of the Covid-19 pandemic…”
Section: Discussion Of the Resultsmentioning
confidence: 51%
“…The results of this study also revealed that the health effects of Covid-19 lockdown on people of Ilorin South Local Government Area in Kwara State differed statistically significantly by gender, age, educational status, and occupation. The study by [37] among Filipino healthcare workers showed that anxiety experienced by participants during the pandemic differed by gender, age, marital status, living status, occupation, work premises and availability of mental health services, while the psychological distress experienced by participants in [35] study also differed by occupation, age, religion and educational status, there was however no statistical difference based on gender among the residents of Myanmar studied. In the present study, there was a disparity in the health effects of Covid-19 lockdown between male and female residents.…”
Section: Discussion Of the Resultsmentioning
confidence: 83%
“…Participants completed the Digital Health Literacy Instrument (DHLI) (8), which was adapted in the context of the COVID Health Literacy Network. The scale measures one's ability to seek, find, understand, and appraise health information from digital resources.…”
Section: Digital Health Literacymentioning
confidence: 99%
“…These measures were effective in reducing both transmission and the overall burden of COVID-19 disease (1). However, research has conclusively shown that COVID-19 has severe health effects including quality of life (2), mental health (3-7), and psychological distress (8)(9)(10)(11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%